To determine the output value of the given function [tex]\( y = 5x + 4 \)[/tex] when the input value is [tex]\( x = -8 \)[/tex], follow these steps:
1. Start with the function [tex]\( y = 5x + 4 \)[/tex].
2. Substitute [tex]\( x = -8 \)[/tex] into the function.
3. Calculate the expression [tex]\( 5(-8) \)[/tex].
Let's go through the calculation:
1. Substitute [tex]\( x = -8 \)[/tex] into the function:
[tex]\[
y = 5(-8) + 4
\][/tex]
2. Multiply [tex]\( 5 \)[/tex] by [tex]\( -8 \)[/tex]:
[tex]\[
5(-8) = -40
\][/tex]
3. Add [tex]\( 4 \)[/tex] to [tex]\( -40 \)[/tex]:
[tex]\[
-40 + 4 = -36
\][/tex]
So, the output value when the input value is [tex]\( -8 \)[/tex] is:
[tex]\[
y = -36
\][/tex]
Thus, the output of the function for [tex]\( x = -8 \)[/tex] is [tex]\( -36 \)[/tex].